Expansion of Industrial crops in Southeast Asia: The case of the oil palm in Indonesia and Malaysia (Huellas, 2020)
The oil palm or African palm (Elaeis guineensis) is a native plant of West Africa. In recent decades, approximately since the sixties, this crop has experienced significant growth in the tropical regions of the southern hemisphere, as a monoculture for the production of vegetable oils for export. Within a context in which oil palm cultivation is expanding into new regions of the world, such as Africa and Central America, research aims to identify the social and environmental problems that the development of industrial oil palm crops has had in the two main oil palm producing countries in the world: Indonesia and Malaysia. It is hypothesized that the expansion of industrial monoculture of oil palm is inserted in the current extractivist paradigm of appropriation of natural resources worldwide; also, that it is responsible for the massive deforestation of tropical forests in Southeast Asia; and that, therefore, it endangers the food sovereignty of the countries of Southeast Asia, by displacing family farming and traditional food crops. The methodology consisted in the survey of academic sources and reports of international organizations and NGOs.
Keywords: oil palm; industrial agriculture; Southeast Asia; food sovereignty